Nurse-Led Cold Compress Therapy to Mitigate Hemodialysis Cannulation Pain: A Descriptive Case Study - Sinta Wijayanti; Lutfiasih Rahmawati; Nur Aminatu Rohima; Fitri Nuriya Santy; Ana Nistiandani (Health and Technology Journal (HTechJ), 2026)
Repeated arteriovenous fistula cannulation induces significant procedural pain in patients undergoing maintenance hemodialysis, necessitating effective, non-pharmacological pain management strategies. This study aimed to evaluate the efficacy of a simple, nurse-led cold compress therapy in reducing cannulation-related pain among patients with chronic kidney disease (CKD). A descriptive case study was conducted in a hospital hemodialysis unit between June and July 2025. Two adult male patients (aged 45 and 53 years) reporting procedural pain were enrolled. Pain intensity was assessed using the Numeric Rating Scale (NRS) at baseline and following two subsequent hemodialysis sessions. The intervention consisted of applying ice cubes enclosed in a rubber glove to the cannulation site for approximately 10 minutes prior to needle insertion. At baseline, patients reported moderate (NRS 6) and severe (NRS 7) pain, respectively. Following the second intervention session, pain scores decreased to 4 and 5. By the third session, pain further diminished to mild levels (NRS 2 and 3). Notably, no adverse cutaneous or systemic events were observed during the application. Pre-cannulation cold compress therapy represents a feasible, low-cost, and safe nurse-led intervention that progressively mitigates hemodialysis cannulation pain. Larger, randomized controlled trials are warranted to validate these preliminary findings, isolate the analgesic effect, and standardize optimal clinical application protocols.